MECHANISM ANALYSIS OF HIGH EMBANKMENTS SLIDINGON THE ROAD IN BANGKINANG, RIAU PROVINCE - Mulyana, Hendra
The excavated slopes and high embankments on roads in Riau Province can reach a height of 25 meters to achieve the elevation design of the Toll Road plan due to the extreme contours of valleys and steep hills. The embankment is planned by forming a slope slump into 1:2 with several traps, each trap height is 5 meters and the bench width between the traps is 2 meters. After being applied to this section of the road, where the total height of the embankment is 20 to 25 meters, the embankment on September 26, 2021. A few days before the incident of sliding, there was heavy rain at the scene with along duration This study aims to analyze the mechanism of high embankment sliding. In analyzing the mechanism of sliding, the condition of the base soil material is considered, the condition of the embankment soil material and the influence of rain intensity. The condition of the basic soil and the condition of the embankment soil are obtained from the results of soil investigation. Rain intensity was analyzed using on-site rain measurement data and taking into account measurement data at the nearest climatology station. From these data, an analysis of the stability of the slopes that are prone to rain was carried out. The analysis was carried out using the principles of soil mechanics for unsaturated soils. Slope stability analysis is performed in a numerical using finite element method-based software. The calculation is carried out by two methods: (i) Total cohesion method and (ii) Extended shear strength method. In the total cohesion method, the contribution of matric suction to the shear strength is calculated as a percentage against pore water pressure under hydrostatic equilibrium conditions. In the extended shear strength method, predictions are made of soil-water characteristic curve (SWCC), permeability function and unsaturated shear strength parameters, ?b. These parameters become the input of soil material in numerical models. Rain intensity is modeled as a flux boundary condition. Analysis of pore water pressure, uw and safety factors, FS since complete embankment to the moment of slope sliding. From the results of the analysis using the total cohesion method, it was found that sliding occurred under the condition of a zero matric suction profile plus a slight increase in groundwater levels at the bottom of the stockpile. The results of the analysis using the extended shear strength method confirm the results of the analysis using the total cohesion method. From the analysis using the extended shear strength method, also obtained variations in pore water pressure, uw and safety factors, FS from the time the stockpile was completed to the time of slope sliding after the rain. From this study, the mechanism of slope sliding due to rain at the location under review can be known. The results of this study can be used in similar cases in the construction of road embankments.